Realitas penatausahaan piutang pajak pemerintah - Dian Pratiwi; Dwi Martani (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2021)
The findings of Audit Board of the Republic of Indonesia (BPK) on tax receivables in the last seven years indicate that the Government has not managed tax receivables properly. This study aims to evaluate problems in the administration of tax receivables at Directorate General of Tax (DGT), make comparisons with other countries, and provide suggestions to solve these problems. The results show several problems in the administration of tax receivables, including systems that are not integrated and real-time, no taxpayer account application, no legal umbrella or clear accounting interpretation for some DGT business processes, lack of human resource discipline in carrying out duties and functions, and lack of supervision.To solve these problems, this study suggested DGT to integrate existing systems, develop taxpayer accounts, improve the quality of human resources and conduct regular supervision, revise PER-08/PJ./2009 and affirm rules for DGT's recurring business processes, and build a data exchange system between the DGT and the Tax Court as well as the DGT and Directorate General of the Treasury.